Correlation between a motion analysis method and Global Operative Assessment of Laparoscopic Skills for assessing interns' performance in a simulated peg transfer task in Jordan: a validation study. - Abdelall, Esraa Saleh; Hamouri, Shadi Mohammad; Al Dwairi, Abdallah Fawaz; Al-Araidah, Omar Mefleh (Journal of Educational Evaluation for Health Professions, 2025)
Purpose: This study aims to validate the use of ProAnalyst (Xcitex Inc.), a software for professional motion analysts to assess the performance of surgical interns while performing the peg transfer task in a simulator box for safe practice in real minimally invasive surgery. Methods: A correlation study was conducted in a multidisciplinary skills simulation lab at the Faculty of Medicine, Jordan University of Science and Technology from October 2019 to February 2020. Forty-one interns (i.e., novices and intermediates) were recruited and an expert surgeon participated as a reference benchmark. Videos of participants' performance were analyzed through the ProAnalyst and Global Operative Assessment of Laparoscopic Skills (GOALS). Two results were s analyzed for correlation. Results: The motion analysis scores by Proanalyst were correlated with those by GOALS for novices (r= -0.62925, P=0.009), and Intermediates (r= -0.53422, P=0.033). Both assessment methods differentiated the participants' performance based on their experience level. Conclusion: The motion analysis scoring method with Proanalyst provides an objective, time-efficient, and reproducible assessment of interns' performance, and comparable to GOALS. It may require initial training and set-up; however, it eliminates the need for expert surgeon judgment.